Health-related outcomes of importance to patients with Takayasu's arteritis - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2018)
Objective. The need to include patients' perspectives as key outcomes in clinical trials is widely accepted. No disease-specific patient-reported outcomes have been developed in Takayasu's arteritis. This project was designed to identify outcomes of importance to patients with Takayasu's arteritis during active disease and remission across 2 different cultures. Methods. Patients with Takayasu's arteritis from the US and Turkey were recruited to participate in semi-structured, one-on-one interviews or focus groups. The interviews and group sessions were recorded, transcribed, and entered into an Nvivo database. A line-by-line review of narrative data was used to develop themes describing the impact of Takayasu's arteritis on patients' life. US Patients were invited to freelist terms that they associated with disease states (active disease and remission). The Smith's Salience Index (SSI) was used to identify the most salient terms. Results. A total of 31 patients with Takayasu's arteritis participated in this study. Interviews and focus groups identified pain, fatigue, and emotional impact as common themes. Outcomes did not differ between the 2 countries. The most salient terms identified through freelisting were pain/discomfort and fatigue/low energy levels (SSI=0.56 and 0.33, respectively) during active disease and pain/discomfort and emotional impact (SSI=0.51 and 0.37, respectively) during remission. Conclusion. Patients with Takayasu's arteritis report a range of disease-specific symptoms across different cultures and disease states that are generally not specifically captured by generic patient-reported outcome tools currently used in research. Identifying disease-specific outcomes would advance clinical trials methodology to best capture the full spectrum of disease activity in Takayasu's arteritis.
Keywords: Takayasu's arteritis; quality of life; patient-reported outcomes; QUALITY-OF-LIFE; RHEUMATOID-ARTHRITIS; CLINICAL-TRIALS